Diagnóstico de la Frontera Ecuador - Colombia - Ecuador. Centro Andino de Estudios Internacionales, Universidad Andina Simón Bolívar, Sede (2016)
This document describes the current situation in Esmeraldas, Carchi, and Sucumbios, all of which are Ecuadorian provinces located on the Colombian border; focusing on four major themes: the institutional presence of the Ecuadorian State, the hottest issues in security, the actual trade flows between Ecuador and Colombia, and the zone's socio-cultural features. The article shows how the Colombian conflict and the Ecuadorian security policy are both affecting the social, political and economic life on the border.